The Effectiveness of Breathing Exercises for Post Covid-19 Patients during Rehabilitation: A Literature Review - T. Widya Naralia; Henny Permatasari (Universitas STRADA Indonesia, 2021)
Covid-19 is a new disease that has become a world pandemic in 2020 untill today. Post covid patients still feel persistent symptoms such as breathlessness, fatigue, and dyspnea even though it has been declared negative from the coronavirus. These persistent symptoms can continue for months and will not disappear immediately but can be relieved by various exercises such as breathing exercises. This literature study aims to identify the types and effect of breathing exercises on persistent symptoms. Literature search was carried out systematically through online databases with the keyword “Breathing Exercise AND Long Covid AND Covid-19 Rehabilitation”. The selected articles were full articles published in 2018-2021 in English and other supporting articles. The result was found 243 articles and 8 articles that met the inclusion and exclusion criteria. There are several deep breathing exercises which is effective in reducing persistent symptoms that is Traditional Chinese exercises, diaphragm and physical exercise.